Power of attorney and contract of agency: comparative legal analysis - Savanets, Lyudmyla (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article carries out a comparative legal analysis of the power of attorney and the contract of agency as security tools for representative relations. Various aspects of the relationship between the power of attorney and the contract of agency are studied. Particular attention is paid to the study of the possibility of issuing a power of attorney in electronic form.The power of attorney and the contract of agency as legal means of implementing the relationship of representation, have much in common, however, their identification is unacceptable.The contract of agency and the power of attorney issued on its basis - constitute a special legal structure, the elements of which are closely related and interact.The main differences between contract of agency and the power of attorney are as follows. The contract of agency can be concluded both orally and in writing. The form of power of attorney is always written. According to the functional criterion, the contract of agency is designed to regulate the relationship between the representative and the principal, while the power of attorney - to inform a third party - the party to the transaction about the powers of the representative. The contract of agency can be both fixed-term and indefinite, i.e., valid for an indefinite period. As a general rule, a power of attorney cannot be indefinite. The grounds for termination of the contract of agency and power of attorney are also excellent.The basis of the relationship of contractual representation is the contract. Thus, the power of attorney acts only as a means of external legitimation of the representative before the third parties, fixes his authority to perform legally significant actions on behalf of the person he represents.Modern challenges of digitalization, the conclusion of a large number of contracts on the Internet makes it necessary to introduce legal instruments that would ensure the efficiency of such contractual relations, simplification and facilitation of civil turnover. The possibility of issuing an electronic power of attorney could be an effective solution to this problem.